EXTRACTING OLIVINE (FO-FA) COMPOSITIONS FROM RAMAN SPECTRAL PEAK POSITIONS - Kuebler K.E.; Jolliff B.L.; Wang A.; Haskin L.A. (My University, 2006)
The dominant feature of the olivine Raman spectrum is a doublet that occurs in the spectral region of 815-825 cm-1 (DB1) and 838-857 cm-1 (DB2). These features arise from coupled symmetric and asymmetric stretching vibrational modes of the constituent SiO4 tetrahedra. The frequencies of both peaks show monotonic shifts following cation substitution between forsterite and fayalite. We present a calibration for extracting olivine Fo contents (Fo = Mg/(Mg + Fe) molar ratio; Fo0-100) from the peak positions of this doublet, permitting estimates of chemical composition from Raman spectra (acquired in the laboratory or field) as well as providing information on crystal structure (distinction of polymorphs). Eight samples spanning the compositional range from forsterite to fayalite were used to develop the calibration equations for the DB1 and DB2 peaks individually and together. The data indicate that the DB1 peak is more reliable for calculating the compositions of Fe-rich olivine but that the DB2 peak is better for magnesian compositions. The two-peak calibration overcomes the limitations of the single-peak calibrations and is capable of calculating olivine compositions to within ±10 Fo units. © 2006 Elsevier Inc. All rights reserved.
Keywords: olivine